The Effectiveness of using the Index Card Match Method to Increasing the Ability of Recognition of Practicum Tools in the Midwife Laboratory in Level I Midwife Students - Mirna Wigunarti; Rizki Rahmawati (POLTEKKES KEMENKES PADANG, 2023)
The process of a midwife to become a competent person begins with taking midwifery education at a midwife education institution. Preliminary study obtained data that students could not name the laboratory equipment and its functions correctly. The results of interviews with students obtained data so far in learning the introduction of laboratory practicum tools using the lecture method. The research was carried out in May-August 2021 and is a quasi-experimental research with a non-equivalent control group design. The research sample was taken using accidental sampling technique totaling 32 respondents who were divided into the intervention group and the control group. The intervention group was given the Index Card Match method and the control group was given the lecture method. Comparison of the effectiveness of the two methods was tested by independent t-test on the value of N-Gain. The result of the research is that there is a difference between Index card match and lecture in improving the ability to recognize laboratory equipment. Based on the N-Gain analysis, the results of the lecture method are less effective and the Index Card Match method is quite effective in increasing the ability to recognize laboratory equipment in students. Index card match is more effective in improving the ability to recognize laboratory equipment compared to the lecture method.